The Marketing Costs And Their Effect On The Marketing Activity In The Industrial Companies: " An Analytical Study In The General Company For Batteries Manufacturing (Al-Mansour Journal, 2022)
The marketing costs have great role in administrating the companies , all their marketing activities and the size oftheir marketing share and finally the continuity of their work and their act of competing against competitors in themarkets. Those costs are considered to be the affected factors in pricing and marketing of production. Theindustrial organization strives to Study the needs of markets, the nature of competion of company’sproductions, effecting the propes mechanism to improve the work of production lines in a way tht meet theexpectations of the company.The current research intrudes an expanding of the concepts of marketing costs and their basic elements andkinds as well. Besides, the merchandising processes and its costs which represents one of the elements ofmarketing mix would be introduced. As far the applicatory aspect, it includes, among other things, the analysis ofstatements issued by the General Company of Batteries Manufacturing for research purpose in consequence ofwhich some conclusions and recommendation that would participate in heightening interest in the elements ofmarketing cost would be duly drawn.